Discrimination between the Two Closely Related Species of the Operational Group B. amyloliquefaciens Based on Whole-Cell Fatty Acid Profiling - Huynh Thu (MICROORGANISMS, 2022)
(1) Background: Bacillus velezensis and Bacillus amyloliquefaciens are closely related members of the “operational group B. amyloliquefaciens”, a taxonomical unit above species level within the ”Bacillus subtilis species complex”. They have similar morphological, physiological, biochemical, phenotypic, and phylogenetic characteristics. Thus, separating these two taxa from each another has proven to be difficult to implement and could not be pushed easily into the line of routine analyses. (2) Methods: The aim of this study was to determine whether whole FAME profiling could be used to distinguish between these two species, using both type strains and environmental isolates. Initially, the classification was determined by partial sequences of the gyrA and rpoB genes and the classified isolates and type strains were considered as samples to develop the identification method, based on FAME profiles. (3) Results: The dissimilarities in 16:0, 17:0 iso, and 17:0 FA components have drawn a distinction between the two species and minor differences in FA 14:0, 15:0 iso, and 16:0 iso were also visible. The statistical analysis of the FA profiles confirmed that the two taxa can be distinguished into two separate groups, where the isolates are identified without misreading. (4) Conclusions: Our study proposes that the developed easy and fast-automated identification tool based on cellular FA profiles can be routinely applied to distinguish B. velezensis and B. amyloliquefaciens.